2017
DOI: 10.7150/thno.17450
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from human platelet-rich plasma prevent apoptosis induced by glucocorticoid-associated endoplasmic reticulum stress in rat osteonecrosis of the femoral head via the Akt/Bad/Bcl-2 signal pathway

Abstract: An excess of glucocorticoids (GCs) is reported to be one of the most common causes of osteonecrosis of the femoral head (ONFH). In addition, GCs can induce bone cell apoptosis through modulating endoplasmic reticulum (ER) stress. Among the three main signal pathways in ER stress, the PERK (protein kinase RNA-like ER kinase)/CHOP (CCAAT-enhancer-binding protein homologous protein) pathway has been considered to be closely associated with apoptosis. Platelet-rich plasma (PRP) has been referred to as a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
264
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(277 citation statements)
references
References 77 publications
12
264
0
1
Order By: Relevance
“…Apoptosis is a normal physiological process that plays an essential role in the progression of ONFH . The endothelium is a crucial site where the control of apoptosis during angiogenesis occurs .…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a normal physiological process that plays an essential role in the progression of ONFH . The endothelium is a crucial site where the control of apoptosis during angiogenesis occurs .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed that PRP promotes the proliferation of HDFs through the activation of ERK1/2 signaling; this was shown by the fact that PRP promotes ERK1/2 phosphorylation, whereas ERK1/2 inhibition eliminates the increase in proliferation triggered by PRP . It has been reported that PRP‐derived exosomes promote cell proliferation by regulating apoptosis through Akt signaling …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSC-derived EVs may induce angiogenesis in ischaemia-related disease [44]. The potential of human platelet-derived EVs in tissue regeneration is also emerging [18,45,46]. …”
Section: Extracellular Vesiclesmentioning
confidence: 99%